The competence of Religious Court in Indonesia and Syahadah Istifadhah (Testimonium De auditu) in Case of Itsbat Waqf - Rifqi Qowiyul Iman (AHKAM : Jurnal Ilmu Syariah, 2018)
This paper examines how exactly the absolute competence of the Religious Courts and the application of syahadah istifadhah (testimonium de auditu) in the case of waqf determination submitted to the Religious Court as a judicial institution under the Supreme Court of the Republic of Indonesia. In the discussion, it is explained how the competence of the Religious Court especially in the case of waqf determination as arranged in Law No. 3 Year 2006 About Religious Courts combined with Law Number 41 Year 2004 About Waqf. In addition, this paper also compares between the concept of syahadah istifadhah and testimonium de auditu also its legal force in the case of verification at the court especially in the case of waqf determination. This paper concludes that the assignment of Waqf is the absolute authority of the Religious Courts. In addition, according to Islamic jursiprudence syahadah istifadhah can be used as a means of proof in waqf determination.